Estudio morfológico y morfométrico del agujero mentoniano mediante evaluación por tomografía computarizada Cone Beam en pacientes adultos dentados - Cabanillas Padilla, Juan (2014)
Abstract Objective. To study the morphology and morphometry of the mental foramen using cone-beam CT in dentate adult patients. Methods. Transversal descriptive study in which 180 cone-beam CTs were studied to analyze the distance between the upper and lower cortical areas of the mental foramen to the alveolar crest and the mandibular basal bone respectively, as well as the location, shape, size and presence of accessory holes. Results. It was found that the mean of the upper cortical area in relation to the alveolar crest was 15.00 mm and the mean of the lower cortical area to the mandibular basal bone was 13.75 mm. The most frequent location was the longitudinal axis of the second premolar (44.4% right side and 47.2% left side). The predominant shape was oval and the size was in the range of 2.00 mm to 2.99 mm. Accessory holes were present in 55.5% of cases. Conclusion. Knowing the exact location of the mental foramen and its variations helps to properly plan surgical procedures and to administer anesthesia effectively without damaging the neurovascular bundle.